THU0528 Decrease in Circulating Visfatin Levels is Associated with Disease Activity Improvement in Early Rheumatoid Arthritis. (10th June 2014) - Hulejová, H.; Sglunda, O.; Mann, H.; Kuklová, M.; Pecha, O.; Pleštilová, L.; Filková, M.; Pavelka, K.; Vencovský, J.; Šenolt, L.
Abstract : Background: Identification of novel molecules contributes to better understanding of rheumatoid arthritis (RA) pathogenesis and offers promise for comprehensive identification of novel biomarkers that would allow monitoring of disease activity and individualize prognosis of RA patients. Visfatin may represent a novel biomarker of disease severity. Serum visfatin levels are elevated in RA, may be associated with the degree of inflammation, clinical disease activity and radiographic joint damage. Objectives: To assess circulating visfatin and its relationship with disease activity and serum lipids in patients with early treatment-naïve RA and to evaluate the effect of treatment with conventional synthetic DMARDs on visfatin levels. Methods: Serum levels of visfatin were analysed in 40 patients with early RA before and after three months of treatment and in 30 age- and sex-matched healthy individuals. Disease activity was assessed by the Disease Activity Score for 28 joints (DAS28) at baseline and at months 3 and 12. Multivariate linear regression analysis was performed to evaluate whether disease activity improvement can be related to serum circulating visfatin or to a change of visfatin levels. Results: Visfatin serum levels were significantly elevated in early RA patients compared with healthy controls (1.92±1.17 vs. 1.36±0.93 ng/ml; p=0.034) and significantly decreased after three months of treatment (to 0.99±0.67 ng/ml; p<0.001). Circulating visfatin and change in visfatin levels correlated with disease activity and disease activity improvement over time, respectively. Visfatin decrease after three months predicted DAS28 improvement after 12 months (p=0.031, adjusted R 2 =10.1%). In addition, decrease of serum visfatin levels was not associated with improved atherogenic index, but was negatively associated with the increase of total cholesterol levels. Conclusions: Short-term decrease in circulating visfatin levels may represent independent predictor of long-term disease activity improvement in patients with early RA. Acknowledgements: This study was supported by Internal Grant Agency of Ministry of Health of the Czech Republic NT/13696-4 and Research Project No. 00023728. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4092